Implementasi Algoritma Quick Sort Pada Aplikasi Pemrograman Berorientasi Objek Berbasis Python Dan Mysql Workbench - Yusuf, Mohamad; Naimah, Faaza (Universitas Mercu Buana, 2025)
This study aims to develop another long-term receivables management system based on Python, using Tkinter for the GUI, and MySQL Workbench as the database administrator. The system development method employs an incremental approach with two main stages: CRUD for basic data management operations and general information presented through data visualization. This study focuses on implementing the performance of the Quick Sort algorithm within an Object-Oriented Programming (OOP) application. The results of system testing with the white-box testing method, using Python Unittest, demonstrate the consistency of functions and logic as expected. The system was tested on 108 cases of other long-term receivables information, successfully providing ease of use, data accuracy, speed of access, and improved information visualization.